Effect of inoculant and enzyme additives on preservation and nutritive value of alfalfa silage - White, J.S.; Bolsen, K.K.; Hart, R.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Lactic acid bacteria (LAB) inoculants and several enzyme additives were evaluated in various combinations using fifth cutting alfalfa. The field-wilted crop was characterized by a high buffer capacity (63.0 meq/100g of DM), low fermentable carbohydrate (5.4% of the DM), and a high number of indigenous LAB (over one million per g). In contrast to several previous studies, the inoculants and enzymes had very little effect on rate and efficiency of fermentation. The 90-d treated silages had similar fiber and digestibility values, compared to the control. Treated silages tended to have higher lactic acid values, but all silages had relatively high acetic acid and ethanol contents, which indicate an inefficient ensiling process.
Keywords: Beef; Alfalfa; Silage; Inoculant; Enzymes